Antecedent Factors And Internet Usage Amongst Undergraduates In Universiti Putra Malaysia - Sapari, Noor Ariffah (2008)

(untitled)
Internet usage is increasing at a phenomenal rate and is being widely discussed throughout the country in trying to achieve the best worldwide. Oblivion to that, the educational sector itself is also no exception. Thus, in an effort to make Internet usage an effective educational tool, it is essential to understand which antecedent factors contribute to the effectiveness of the Internet usage amongst undergraduates. This research was an attempt to study on the antecedents’ factors and Internet usage amongst students of UPM. The main objective of this study is to investigate the antecedents factors associated with the Internet usage amongst students in UPM. There were fifteen research questions posed in order to achieve the objectives. The antecedents factors that were accessed were Individually (Internet experience, Internet playfulness), Institutionally (Organizational support) and Internet Attitudes and Beliefs (Internet Self –Efficacy, Attitude towards Internet & Internet Satisfaction). The Internet usage was based on time, frequency and activities accessed. With the research framework based on the Theory of Reasoned Action (TRA), Technology Acceptance Model (TAM) and IT Diffusion Process Model, a survey was conducted amongst final year undergraduates of UPM to explore these issues. The research design was a descriptive research and the data were collected using questionnaires. Both descriptive (percentage & frequency) and inferential statistics (t- test & Pearson correlation) were used to analyze the data of the study. A pilot test was conducted and the reliability coefficient for the instrument was high as each section ranges from 0.782 – 0.859. This quantitative descriptive research involved 361 final year undergraduates of UPM. The research findings indicated that in general most undergraduates can be considered experienced Internet users as they have used the Internet for more than five years with looking for general information being the main activity whilst on the Internet. Though results showed no significance difference for time spent on the Internet and in the Internet activities between the male and female students and between the science and non-science streams but there was a significance difference in their frequency. Pearson correlation analysis indicated that there was a low positive correlation between Internet usage and the antecedents. This is also similar with the correlation between Internet usage and impact of the Internet. Thus, based on the findings of this study, it is therefore crucial to look into other factors that would actually utilize the maximum usage of the Internet rather than having the technology but not using it to its fullest potential.